Evidence of viscerally‐mediated cold‐defence thermoeffector responses in man. (26th December 2016) - Morris, Nathan B.; Filingeri, Davide; Halaki, Mark; Jay, Ollie
Abstract : Key points: Visceral thermoreceptors that modify thermoregulatory responses are widely accepted in animal but not human thermoregulation models. Recently, we have provided evidence of viscerally‐mediated sweating alterations in humans during exercise brought about by warm and cool fluid ingestion. In the present study, we characterize the modification of shivering and whole‐body thermal sensation during cold stress following the administration of a graded thermal stimuli delivered to the stomach via fluid ingestion at 52, 37, 22 and 7°C. Despite no differences in core and skin temperature, fluid ingestion at 52°C rapidly decreased shivering and sensations of cold compared to 37°C, whereas fluid ingestion at 22 and 7°C led to equivalent increases in these responses. Warm and cold fluid ingestion independently modifies cold defence thermoeffector responses, supporting the presence of visceral thermoreceptors in humans. However, the cold‐defence thermoeffector response patterns differed from previously identified hot‐defence thermoeffectors. Abstract: Sudomotor activity is modified by both warm and cold fluid ingestion during heat stress, independently of differences in core and skin temperatures, suggesting independent viscerally‐mediated modification of thermoeffectors. The present study aimed to determine whether visceral thermoreceptors modify shivering responses to cold stress. Ten males (mean ± SD: age 27 ± 5 years; height 1.73 ± 0.06 m, weight 78.4 ± 10.7 kg) underwent whole‐body cooling via a water perfusion suit at 5°C, on four occasions, to induce a steady‐state shivering response, at which point two aliquots of 1.5 ml kg –1 (SML) and 3.0 ml kg –1 (LRG), separated by 20 min, of water at 7, 22, 37 or 52°C were ingested. Rectal, mean skin and mean body temperature ( T b ), electromyographic activity (EMG), metabolic rate (M) and whole‐body thermal sensation on a visual analogue scale (WBTS) ranging from 0 mm (very cold) to 200 mm (very hot) were all measured throughout. T b was not different between all fluid temperatures following SML fluid ingestion (7°C: 35.7 ± 0.5°C; 22°C: 35.6 ± 0.5°C; 37°C: 35.5 ± 0.4°C; 52°C: 35.5 ± 0.4°C; P = 0.27) or LRG fluid ingestion (7°C: 35.3 ± 0.6°C; 22°C: 35.3 ± 0.5°C; 37°C: 35.2 ± 0.5°C; 52°C: 35.3 ± 0.5°C; P = 0.99). With SML fluid ingestion, greater metabolic rates and cooler thermal sensations were observed with ingestion at 7°C (M: 179 ± 55 W, WBTS: 29 ± 21 mm) compared to 52°C (M: 164 ± 34 W, WBTS: 51 ± 28 mm; all P < 0.05). With LRG ingestion, compared to shivering and thermal sensations with ingestion at 37°C (M: 215 ± 47 W, EMG: 3.9 ± 2.5% MVC, WBTS: 33 ± 2 mm), values were different (all P < 0.05) following ingestion at 7°C (M: 269 ± 77 W, EMG: 5.5 ± 0.9% MVC, WBTS: 14 ± 12 mm), 22°C (M: 270 ± 86 W, EMG: 5.6 ± 1.0% MVC, WBTS: 18 ± 19 mm) and 52°C (M: 179 ± 34 W, EMG: 3.3 ± 2.1% MVC, WBTS: 53 ± 28 mm). In conclusion, fluid ingestion at 52°C decreased shivering and the sensation of coolness, whereas fluid ingestion at 22 and 7°C increased shivering and sensations of coolness to similar levels, independently of core and skin temperature. Key points: Visceral thermoreceptors that modify thermoregulatory responses are widely accepted in animal but not human thermoregulation models. Recently, we have provided evidence of viscerally‐mediated sweating alterations in humans during exercise brought about by warm and cool fluid ingestion. In the present study, we characterize the modification of shivering and whole‐body thermal sensation during cold stress following the administration of a graded thermal stimuli delivered to the stomach via fluid ingestion at 52, 37, 22 and 7°C. Despite no differences in core and skin temperature, fluid ingestion at 52°C rapidly decreased shivering and sensations of cold compared to 37°C, whereas fluid ingestion at 22 and 7°C led to equivalent increases in these responses. Warm and cold fluid ingestion independently modifies cold defence thermoeffector responses, supporting the presence of visceral thermoreceptors in humans. However, the cold‐defence thermoeffector response patterns differed from previously identified hot‐defence thermoeffectors.